La paz: de la Séptima Papeleta al Estado constitucional y al reconocimiento como derecho fundamental (2016)
This article presents a theoretical approach of the fundamental right to peace enshrinedin the 1991 Constitution in Article 22, from a historical look at the mainprecedent in the process of shaping the new constitutional model, which was thecontribution is presented to it the student movement as a promoter of the seventhballot, then going to expose the state model that is adopted and the differentexpressions of the same can be given, then finally get to review how the state andthe Constitution are aimed at recognizing peace as a right and duty and may havelegal standard scope and as state policy.